Covid-19 Prevention Behavior Model at CV. SST Bandung in 2022 - Fauziah, Diah Adni; Puspita, Nike (MOLUCCAS HEALTH JOURNAL, 2022)
Novel coronavirus (2019-nCoV) is a new type of coronavirus that has never been previously identified in humans that can cause illness ranging from the common cold to serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). COVID-19 spreads from person to person especially when an infected person comes in contact with other people. The purpose of this study was to figure COVID-19 prevention behavior model in workers at CV. SST Bandung, Indonesia. The type of research is observational analytic using a cross sectional design. Stratified random sampling technique with 63 respondents. The research instrument used a questionnaire with validity and reliability test. Data analysis using Linear regression. The model showed that knowledge, social support, OHS communication, and supervision could be explained varians of prevention behavior of 30.1%. Knowledge has the stronger association with prevention behavior. CV. SST should be increasing workers’s awareness of COVID-19 with any interesting education media and supervision in several times of year